When stones deceive: A case report of renal calculus mimicking upper tract malignancy (Indian Journal of Case Reports, 2025)
Renal cell carcinoma often presents with hematuria and flank pain, symptoms that overlap with benign urological conditions like nephrolithiasis. In this case report, we describe a 35-year-old male with flank pain and a suspicious renal mass identified on imaging, initially raising concerns for malignancy. A detailed evaluation, including retrograde pyelography and flexible ureteroscopy, ultimately revealed a staghorn calculus rather than malignancy with inflammatory changes, which was successfully treated with percutaneous nephrolithotomy. This case underscores the importance of comprehensive evaluation to avoid misdiagnosis and overtreatment in patients with renal stones mimicking malignancy.